2006
DOI: 10.1063/1.2200746
|View full text |Cite
|
Sign up to set email alerts
|

Full spectrum enhancement of the light harvesting efficiency of dye sensitized solar cells by including colloidal photonic crystal multilayers

Abstract: Herein we report a theoretical analysis of the efficiency of dye sensitized solar cells in which colloidal crystals are introduced in different configurations. We find that piling up different lattice constant crystals leads to light harvesting enhancement in the whole dye absorption range. We provide the optimum structural features of such photonic crystal multilayer needed to achieve a photocurrent efficiency enhancement of around 60% with respect to standard dye sensitized solar cells. We demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 15 publications
2
83
0
Order By: Relevance
“…In these specific experiments, DSSC required an opal with a lattice parameter that gives red photocurrent enhancement. Additionally it is possible to couple two or more 3DPC with different lattice parameters to enhance photocurrent in a wider spectral range (Mihi et al, 2006). Since this effect was confirmed theorically, we can mention that the disadvantage of these materials is the several steps involved to achieve these types of structures.…”
Section: Three Dimensional Ordered Structuresmentioning
confidence: 94%
“…In these specific experiments, DSSC required an opal with a lattice parameter that gives red photocurrent enhancement. Additionally it is possible to couple two or more 3DPC with different lattice parameters to enhance photocurrent in a wider spectral range (Mihi et al, 2006). Since this effect was confirmed theorically, we can mention that the disadvantage of these materials is the several steps involved to achieve these types of structures.…”
Section: Three Dimensional Ordered Structuresmentioning
confidence: 94%
“…Miguez et al [13] suggested that photoelectric conversion efficiency could be improved by utilising an inverse opal with a particle size of approximately 200 nm. However, we found that IO356 exhibited the highest overall photoelectric conversion efficiency and the highest photoelectric conversion efficiency per one dye molecule.…”
Section: Resultsmentioning
confidence: 99%
“…In 2006, Miguez et al theoretically discussed the light harvesting effect of TiO 2 inverse opals in DSSCs [13,14]. They demonstrated that the light harvesting was the result of the optical absorption amplification effect of slow photon resonant modes partially confined within the absorbing part of the cell due to the mirror behaviour of the colloidal superlattice.…”
Section: Introductionmentioning
confidence: 99%
“…To confer order to the scattered light, Miguez proposed the selective mirror for DSC (Colodrero et al, 2009a) made out from colloidal TiO 2 suspensions (Wijnhoven & Vos, 1998;Colodrero et al, 2008). They consist in photonic crystals (PCs) (Yip et al, 2008;Colodrero et al, 2009b), introduced either inside the titania layer or on its backside (Nishimura et al, 2003;Mihi et al, 2006), currently under an intense experimentation. Scheme in Fig.…”
Section: Photon Managementmentioning
confidence: 99%